Samaria Veg creacion de una panaderia vegana y vegetariana en la ciudad de Santa Marta (2023)
SAMARIAN VEG, vegan and vegetarian bakery is a business proposal that seeks to correct and innovate the bakery sector of Santa Marta, Colombia.This project was born from the need to promote the vegan market in the Samarian population by bringing to their tables a product with high quality, flavor and an affordable value that they can enjoy as a family, with the satisfaction that they are tasting of a food that will give benefits to their health, SAMARIAN seeks to generate a gastronomic impact on the population, since by offering products with low levels of sugars and high nutrient centered, it will generate the awakening of the vegan and vegetarian population that is based or visiting in the most beautiful bay in America, being a tourist city will have a greater boom in the visiting population, generate an optimal service and at the hand of all those who want to try a new experience with the best flavor, price and above all healthy for you and your family.